Nursing intervention of Head Up 30° position to reduce intracranial pressure in ICH patients in the Nusa Indah room of Dr. Doris Sylvanus Hospital Palangka Raya - Hartati, Sri; Datak, Gad; Missesa; Sylvia, Ester Inung (Journal of Midwifery and Nursing, 2025)
Intracerebral Hemorrhage (ICH) is a medical emergency characterized by bleeding in the brain tissue, which can increase intracranial pressure (ICP) and risk causing death or severe neurological disability. One non-invasive nursing intervention to reduce ICP is the position of the head-up 30° which can increase blood flow to the brain thereby contributing to changes in Mean Arterial Pressure (MAP) and oxygen saturation (SpO2). This study aims to determine the effectiveness of implementing the 30° head-up position intervention to reduce MAP and increase SpO2 in hemorrhagic stroke patients with ICH. This research design is an application of Evidence Based Nursing Practice (EBNP) using a case study approach. The number of patients is 2 people according to the main EBNP journal. The intervention given is a 30° head-up position carried out in the morning and afternoon for 30 minutes each for 3 days. MAP and SpO2 measurements were carried out before and after the 30° head-up intervention for 3 days. The results of the 30° head-up intervention showed an average decrease in MAP in both patients of around 11–12 mmHg and an increase in SpO2 of around 1.5–2.5%. This indicates that the nursing intervention of 30° head-up positioning is proven to be effective in helping to reduce intracranial pressure  in hemorrhagic stroke patients with ICH. The results of the application of this EBNP have limitations due to the limited number of patients implemented, the short time of implementation of the intervention and consideration of other factors that influence.